1994
DOI: 10.1524/ract.1994.65.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Nickel and Cobalt on a Size-Fraction of Unconsolidated Glaciofluvial Deposits and on Clay Minerals

Abstract: In earlier studies we investigated the sorption behaviour of cesium, barium and strontium on size fractions of glaciofluvial materials and on the clay minerals montmorillonite, illite and chlorite. Here, we report on sorption and desoiption experiments with nickel and cobalt in synthetic groundwater on the <32 μπι size-fraction of a glaciofluvial deposit, on the clay minerals montmorillonite and illite, and on synthetic Si0 2 and CaC0 3 . In general, sorption and desorption equilibrium is not reached for nicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This assumption is often valid in the case of organic chemicals, but it is not always justified in the case of inorganic chemicals where sorption may be at least partly irreversible. Sorption and desorption experiments with zinc, nickel, cobalt, strontium, and cesium on natural soils and clay minerals were conducted to estimate the reversibility of sorption and the mobility of metals of concern in an aqueous solution (5,11,22,23). The reversibility of Pb sorption on clinoptilolite was examined as a function of other exchange cations present in the zeolite structure (20).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is often valid in the case of organic chemicals, but it is not always justified in the case of inorganic chemicals where sorption may be at least partly irreversible. Sorption and desorption experiments with zinc, nickel, cobalt, strontium, and cesium on natural soils and clay minerals were conducted to estimate the reversibility of sorption and the mobility of metals of concern in an aqueous solution (5,11,22,23). The reversibility of Pb sorption on clinoptilolite was examined as a function of other exchange cations present in the zeolite structure (20).…”
Section: Introductionmentioning
confidence: 99%
“…They found a considerable mobility for "Tc, 60 Co and 233 U which they attributed to low molecular weight anionic complexing. Another plausible explanation could be based on batch laboratory experiments by Griitter et al [223], who found, with selected size fraction of clay minerals and glaciofluvial sediments, that the sorption kinetics of cobalt and nickel is very slow. In contrast, the concentrations of 90 Sr and 137 Cs were extremely low in the groundwater due to an artificial alkaline environment near the trench which enhanced sorption and precipitation of '"Sr, and the strong and selective sorption of 137 Cs to illite.…”
Section: Groundwatersmentioning
confidence: 99%